2010
DOI: 10.1039/c0gc00192a
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose conversion into alkylglycosides in the ionic liquid 1-butyl-3-methylimidazolium chloride

Abstract: The conversion of cellulose into alkylglycosides is carried out in the ionic liquid 1-butyl-3-methylimidazolium chloride in the presence of an acidic catalyst. Primary alcohols like n-butanol and n-octanol were used as alkylating reagents. The acidic resin Amberlyst 15DRY proved to be the optimum heterogeneous catalyst: it catalyzes the hydrolysis of the b(1→4) links in the cellulose polymeric chain as well as the alkylation of the hydroxyl groups at the C1 position of the glucose intermediate. The cellulose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 51 publications
0
28
1
Order By: Relevance
“…Furthermore, successful alkyl glucoside production was observed even for long-chain alcohols such as 1-dodecanol. [10d] This is in contrast to the one-step experiments reported by de Vos and co-workers, [11] for which no products were obtained from cellulose and 1-dodecanol, though the reaction worked well with shorter chain alkanols.…”
Section: Introductioncontrasting
confidence: 77%
“…Furthermore, successful alkyl glucoside production was observed even for long-chain alcohols such as 1-dodecanol. [10d] This is in contrast to the one-step experiments reported by de Vos and co-workers, [11] for which no products were obtained from cellulose and 1-dodecanol, though the reaction worked well with shorter chain alkanols.…”
Section: Introductioncontrasting
confidence: 77%
“…Studies have been done on various chemical reactions being catalyzed by Amberlyst 15, like synthesis of levulinic acid from fructose [8], synthesis of pyrazolines [9], conversion of cellulose into cellulose acetate [10], conversion of cellulose into biodegradable surfactants like octyl-␣,␤-glucoside and octyl-␣,␤-xyloside [11] etc. Amberlyst 15 has also been known to aid the hydrolysis of ˇ(1→4) linkage of the cellulose backbone [12]. Very few studies have been done on biomass hydrolysis using Amberlyst though it has been reported for hydrolysis of cellulose.…”
Section: Introductionmentioning
confidence: 98%
“…Hydrolysis time was found to be an important factor for the Fischer glycosidation step, with 1.5 h hydrolysis of cellulose shown to be the optimum hydrolysis time with a yield ~82 % of n-octanol-α,β-glucosides, and 98 % conversion of cellulose was obtained. Interestingly Ignatyev et al also fi nished a similar work using BMIMCl which produced an 86 % yield of butyl glycosides from the reaction of n-butanol with cellulose over an Amberlyst-15 catalyst [ 135 ]. The effect of hydrolysis time was also investigated but found that 4 h was the optimal hydrolysis time for cellulose, which may be due to the different reaction conditions.…”
Section: Glycosidation Of Cellulose To Alkyl Glucosidesmentioning
confidence: 95%